PEDAGOGICAL PRACTICE OF TECHNICAL UNIVERSITY POSTGRADUATES: TRADITION AND INNOVATIONS - E. I. Muratova; N. V. Molotkova (Высшее образование в России)
The article presents the technology for development of technical university post-graduates’ readiness for teaching activities in the system of higher education. Traditional and innovative approaches to the organization of post-graduates pedagogical training are considered. The authors have carried out an analysis of more than 100 programmes of pedagogical competencies formation presented in postgraduate courses at different universities and research institutes. There are notable differences in treatment of certain stages of postgraduates’ pedagogical training (pedagogical disciplines, their place in educational programme structure, workload, assessment) and the requirement to learning outcomes presented in pedagogical competences. But all the programmes emphasize the importance of practical teaching experience in the process of pedagogical competence development. The paper shows the role of the pedagogical courses, pedagogical training, midterm and final assessments for the formation of competencies required for the qualification “Teacher-researcher”. The authors also discuss the necessity of development of postgraduates’ research competencies and their professional and personal self-development skill during the pedagogical practice period. The paper substantiates the importance of the transition from the educational-methodological and scientificdescriptive models of future teacher professional activity to the scientific-pedagogical one. Recommendations on the organization of postgraduate pedagogical training are given and the experience of its organization at Tambov State Technical University is generalized.